(untitled) (Proceedings of the International Conference on Education, 2025)
This research aims to progress students’ mathematics learning achievement through the application of a problem-based learning model demonstrate helped by live worksheets in class XII of Budi Mulia Dua Vocational High School for the 2024/2025. This research is classroom action research carried out in 2 cycles. Each cycle consists of planning, action, observation, and reflection. The research subjects were 20 students in class XII of Budi Mulia Dua Vocational High School for the 2024/2025. Research data was obtained through tests, observation and documentation. Data analysis uses qualitative descriptive analysis techniques. Data validation uses triangulation method. The results of the research show that there is an increase in the learning outcomes of students at XII Budi Mulia Vocational High School for the 2024/2025 academic year through the application of the problem learning model assisted by live worksheets. The increase in learning outcomes is shown by an increase in the average percentage of achievement of mathematics learning outcomes from 44.5 in pre-cycle to 70.83 in cycle 1, then increasing to 76.9 in cycle 2. Based on these results it can be concluded that there is an increase in student learning achievement in mathematics lessons, especially statistics material with the problem-based learning model demonstrate helped by live worksheets. The integration of liveworksheets in syntax PB, can increase student enthusiasm and interests. The limitation of this study is the small sample size, which means there is potential for bias in data collection. In addition, this study is also limited to statistical material.